Philip Pullman’s Northern Lights: Exploring Children and Myths as the Intrinsic Formulation in an Adventure Story - M. Yuseano Kardiansyah (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2023)
This study investigates a novel entitled Northern Lights (1995), authored by Philip Pullman as a fantasy fiction in the context of popular literature. The aim of this study is to reveal the significance of children and myth characters as the formula and the intrinsic formulation of this novel as an adventure story. As a textual study, this study uses a narrative analysis method that can help to explore the intrinsic elements of prose fiction. The relevant data collected and analyzed in this study are narrations or dialogues that refer to particular acts and speech of characters, settings of place, theme, and plot in the novel. All data are analyzed to disclose the conception of children and myths used as the basic formula of this novel. At the end of the analysis, the investigation reveals the significance of children and myth characters in this novel. They are seemingly used to attract readers’ interest and concern in transcending their imagination boundaries in their daily lives. Besides, this study can also explicate how they are intrinsically formulated in an adventure story.